A Researchers Paradise: High Quality Services on the Internet for Research and Life-long Learning - Burchardt, Jørgen (Proceedings of the International Conference on Networked Learning, 2002)
Services for research are still in the early days of development and adoption by scholars. Over the next years many new methods will emerge. These new scholarly resources may be very different in form and function than their current manifestations. Focus will be on research as such. The first part of the paper will outline its relations to learning, e-learning and knowledge management. A theoretical framework will be presented within which the new possibilities for the development of the research can be understood. This paper is then a preliminary attempt to map out some of the key contexts within which the scholarly resources will exist. I will examine the emerging role and fit of the different services in scholarly scientific practice - including examples of the ‘best practice’ within the field- the range of dimensions that shape their usage and provide value for scholars, and the larger impact on scholarly practice. In the final section, I present insights on the adoption and implications for the future.